Penerokaan persediaan kerjaya Kaunselor dalam kalangan Mahasiswa Kaunseling Tahun Satu Universiti Malaysia Sarawak - Marcos, Jamal (Universiti Malaysia Sarawak, (UNIMAS), 2019)
This study was conducted to explore the career counsellor in preparation among undergraduate counselling year one Universiti Malaysia Sarawak (UNIMAS). There are three objectives reviewed in this study which are the perception of interest in the career counsellor in student counselling year one UNIMAS, explore a career counsellor in the perception of knowledge among the undergraduates in year one of counselling UNIMAS, and explores the extent to which perception preparation career as counsellor counselling among the undergraduates in year one UNIMAS. This study was carried out at the Faculty of Cognitive Sciences and human development, Universiti Malaysia Sarawak. There are six respondent consist of three women and three men. This study uses qualitative methods and design case study. Interview is being held as the method of this research and they need to answer some questions during interviewing. All the data and answers from the respondent will keep as a confidential. Data from the interviews will be analysed using the domain method which and will be expanded to become a taxonomy according to themes. Outcome from the studies show that students year one have shown an interest toward counselling program and it is influenced by two factors, in term of intrapersonal and interpersonal. In addition, students gain knowledge what is career counsellor from their counsellor teacher at school. From the study, it is show that students are ready to become a professional counsellor in the future. All research findings are consistent with previous studies and supported by the theory of Cognitive Information Processing (CIP).